Pediatrik Kulak Burun Boğaz Hastalıkları - Gergin, Özgül; Erkmen, Burak; Ünsal, Melike Pınar; Yıldırım Özkan, Pınar; Baysal Çitil, Ahu; Çubuk, Hüseyin; Fındık, Mahmut Ozan; Akufuk, Caner; Gedik, Muhammed Semih; Cırık, Ahmet Adnan; Esen Yiğit, Yeşim; Akgün Bostancı, Şeyma; et al. (Academician Publishing Book DOI Portal, 2024)
-